Impact of three Decades of Antiretroviral Therapy in a Longitudinal Population Cohort Study. Issue 3 (April 2019) - Hanhoff, Nikola; Vu, Quang; Lang, Raynell; Gill, M John
Background: We have used a comprehensive HIV population to characterize antiretroviral therapy (ART), drug class selection, pill burden, drug costs and health outcomes over the entire span of the HIV epidemic. Methods: Antiretroviral (ARV) use (drugs, classes, formulations) and both the laboratory and clinical outcomes (HIV-1 RNA, CD4 + T-cell count and mortality) were determined for all patients in Southern Alberta, Canada, at each year-end between 1986 and 2017. Pill burden, cumulative drug exposure and costs were calculated for each year. Results: The number of ARV-treated patients increased from 29.6% (77/260) in 1989 to 93.4% (1, 814/1, 943) in 2017. Regimen selection showed continuous adjustments for toxicity, resistance, pill burden and adherence. Dramatic improvements in outcomes were seen. In 1997, 22.4% of treated patients had an undetectable viral load, this has been consistently around 90% since 2010 (92.7% in 2017). While HIV-related annual mortality rate declined from 11.0% in 1994 to 0.1% in 2017, all-cause mortality remained relatively stable from 1997 onwards. ART pill burden escalated in 1997 (12.4/day), then decreased to 2.1/day in 2016. Mean ART cost increased in 1997 (CAN905/month/regimen in 1997, 1, 223 in 2016). Mean cumulative lifetime exposure to protease inhibitors is 5.98 ±4.9 and to nucleoside reverse transcriptase inhibitors 8.8 ±6.2 years. Conclusions: Our findings demonstrate not only the immense burden that HIV has imposed on both patients and society, but also the substantial benefit of ART on patient outcomes. They show that research, patient engagement and programme support can with time minimize the harmful long-term effects of HIV-infection.